From Lombard Street to Avenida Paulista : Foreign Exchange Liquidity Easing in Brazil in Response to the Global Shock of 2008-09 - Stone, Mark.; Walker, W. Christopher; Yasui, Yosuke (Washington, D.C. : International Monetary Fund, 2009)
The provision of foreign exchange liquidity by emerging market central banks during the global shock of 2008-09 departs from the domestic liquidity lender of last resort role described by Bagehot in his classic "Lombard Street." This paper documents and analyzes the foreign exchange liquidity providing measures of the Banco Central do Brasil (BCB) in response to varied market stresses. These measures appear to have reduced the relative onshore cost of dollar liquidity on impact and seemed to stabilize market expectations of exchange rate volatility. The results suggest that foreign exchange liquidity easing operations may become a standard central bank tool.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet